CSE 311 Lecture 15:
Modular Exponentiation and Induction

Emina Torlak and Kevin Zatloukal

Topics

Modular equations
A quick review of Lecture 14.
Modular exponentiation
A fast algorithm for computing $a^k\ \text{mod}\ m$.
Mathematical induction
A method for proving statements about all natural numbers.
Using induction
Using induction in formal and English proofs.
Example proofs by induction
Example proofs about sums and divisibility.

Modular equations

A quick review of Lecture 14.

Bézout’s theorem and multiplicative inverses

Bézout’s theorem
If $a$ and $b$ are positive integers, then there exist integers $s$ and $t$ such that $\gcd{a}{b} = sa + tb$.

We can compute $s$ and $t$ using the extended Euclidean algorithm.

If $\gcd{a}{m} = 1$, then $\mod{s}{m}$ is the multiplicative inverse of $a$ modulo $m$:

  • $1 = \mod{(sa+tm)}{m} = \mod{sa}{m}$, so we have
  • $\congruent{sa}{1}{m}$.

These inverses let us solve modular equations.

Using multiplicative inverses to solve modular equations

Solve: $\congruent{7x}{1}{26}$

① Compute GCD and keep the tableau.

② Solve the equations for $r$ in the tableau.

$a$ $=$ $q$ $*$ $b$ $+$ $r$
$26$ $=$ $3$ $*$ $7$ $+$ $5$
$7$ $=$ $1$ $*$ $5$ $+$ $2$
$5$ $=$ $2$ $*$ $2$ $+$ $1$
$r$ $=$ $a$ $-$ $q$ $*$ $b$
$5$ $=$ $26$ $-$ $3$ $*$ $7$
$2$ $=$ $7$ $-$ $1$ $*$ $5$
$1$ $=$ $5$ $-$ $2$ $*$ $2$

③ Back substitute the equations for $r$.

④ Solve for $x$.

  • Multiplicative inverse of 7 mod 26
    • $\mod{(-11)}{26}=15$
  • So, $x=26k + 15$ for $k\in\Z$.

Solving a more general equation

Solve: $\congruent{7y}{3}{26}$

We computed that 15 is the multiplicative inverse of 7 modulo 26:
That is, $\congruent{7 * 15}{1}{26}$.
By the multiplication property of mod, we have
That is, $\congruent{7 * 15 * 3}{1 * 3}{26}$.
So, any $\congruent{y}{15 * 3}{26}$ is a solution.
That is, $y = 19 + 26k$ for any $k\in\Z$ is a solution.

A useful proof technique based on modular equations

Suppose that $x,y\in\Z$ and $(x, y)$ satisfies linear equations
$ax + by = c$ and $dx + ey = f$,
where $a,b,c,d,e,f$ are integer coefficients.
Then $(x, y)$ also satisfies the corresponding equations mod $m > 0\in\Z$:
$\congruent{ax + by}{c}{m}$ and $\congruent{dx + ey}{f}{m}$.
The reverse doesn’t hold. Can you think of a counterexample?
$(0, 0)$ is a solution to $\congruent{x + y}{2}{2}$ and $\congruent{2x + 2y}{4}{2}$.
But it’s not a solution to $x + y = 2$ and $2x + 2y = 4$.
The contrapositive is a useful proof technique:
You can prove that a system of linear equations with integer coefficients has no integer solutions by showing that those equations modulo $m$ have no solutions.

Modular exponentiation

A fast algorithm for computing $a^k\ \text{mod}\ m$.

The modular exponentiation problem: $\mod{a^k}{m}$

How would you compute $\mod{78365^{81453}}{104729}$?

Naive approach
First compute ${78365^{81453}}$.
Then take the result modulo $104729$.
This works but is very inefficient …
The intermediate result ${78365^{81453}}$ is a 1,324,257-bit number!
But we only need the remainder mod 104,729, which is 17 bits.

To keep the intermediate results small, we use fast modular exponentiation.

Repeated squaring: $\mod{a^k}{m}$ for $k = 2^i$

If $k = 2^i$, we can compute $\mod{a^k}{m}$ in just $i$ steps.

Note that $\congruent{\mod{a}{m}}{a}{m}$ and $\congruent{\mod{b}{m}}{b}{m}$. So, we have $\mod{ab}{m} = \mod{((\mod{a}{m})(\mod{b}{m}))}{m}$.

For example:

What if $k$ is not a power of 2?

Fast exponentiation: $\mod{a^k}{m}$ for all $k$

Note that 81453 is 10011111000101101 in binary.
$81453 = 2^{16} + 2^{13} + 2^{12} + 2^{11} + 2^{10} + 2^{9} + 2^{5} + 2^{3} + 2^{2} + 2^{0}$
$a^{81453} = a^{2^{16}} * a^{2^{13}} * a^{2^{12}} * a^{2^{11}} * a^{2^{10}} * a^{2^{9}} * a^{2^{5}} * a^{2^{3}} * a^{2^{2}} * a^{2^{0}}$

Fast exponentiation computes $\mod{a^k}{m}$ using $\leq 2\log k$ multiplications mod $m$.

The fast exponentiation algorithm

Example implementation:

// Assumes a > 0, k >= 0, m > 0.
public static long fastModExp(long a, long k, long m) {
    if (k == 0) {            // k = 0
        return 1;
    } else if (k % 2 == 0) { // k is even
        long tmp = fastModExp(a, k/2, m);
        return (tmp * tmp) % m;
    } else {                // k is odd
        long tmp = fastModExp(a, k-1, m);
        return (a * tmp) % m;
    }
}

$\mod{78365^{81453}}{104729} = 45235$

Using fast modular exponentiation: RSA encryption

Alice chooses random 512-bit (or 1024-bit) primes $p, q$ and exponent $e$.
Alice computes $m=pq$ and broadcasts $(m, e)$, which is her public key.
She also computes the multiplicative inverse $d$ of $\mod{e}{(p-1)(q-1)}$, which serves as her private key.
To encrypt a message $a$ with Alice’s public key, Bob computes $C = \mod{a^e}{m}$.
This computation uses fast modular exponentiation.
Bob sends the ciphertext $C$ to Alice.
To decrypt $C$, Alice computes $\mod{C^d}{m}$.
This computation also uses fast modular exponentiation.
It works because $\mod{C^d}{m} = a$ for $0 < a < m$ unless $p\vert a$ or $q \vert a$.

Mathematical induction

A method for proving statements about all natural numbers.

How would you prove this theorem?

Mods and exponents
For all integers $a, b, m > 0$ and $k \geq 0$, $\congruent{a}{b}{m} \rightarrow \congruent{a^k}{b^k}{m}$.
Proof (almost):
Let $a, b, m > 0\in\Z$ and $k \geq 0\in\Z$ be arbitrary. Suppose that $\congruent{a}{b}{m}$.
By the multiplication property, we know that if $\congruent{a}{b}{m}$ and $\congruent{c}{d}{m}$, then $\congruent{ac}{bd}{m}$. So, taking $c$ to be $a$ and $d$ to be $b$, we have $\congruent{a^2}{b^2}{m}$.
Applying this reasoning repeatedly, we have
This, uhm, completes the proof? $\qed$

We don’t have a proof rule to say “perform this step repeatedly.”

Perform a step repeatedly with induction!

Induction$\rule{P(0); \forall k. P(k)\rightarrow P(k+1)}{\forall n. P(n)}$

Domain: natural numbers ($\N$).

Induction is a logical rule of inference that applies (only) over $\N$.
If we know that a property $P$ holds for 0, and
we know that $\forall k. P(k)\rightarrow P(k+1)$, then
we can conclude that $P$ holds for all natural numbers.
// f(x) = x for all x >= 0.
public int f(int x) {
  if (x == 0) { return 0; }
  else        { return f(x - 1) + 1; }
}

Induction is essential for reasoning about programs with loops and recursion.

Induction: how does it work?

Induction$\rule{P(0); \forall k. P(k)\rightarrow P(k+1)}{\forall n. P(n)}$

Domain: natural numbers ($\N$).

Suppose that we are given $P(0)$ and $\forall k. P(k)\rightarrow P(k+1)$.

How does that give us $P(k)$ for a concrete $k$ such as $5$?

1. First, we have $P(0)$. $P(0)$
2. Since $P(k)\rightarrow P(k+1)$ for all $k$, we have $P(0)\rightarrow P(1)$. $\ \Downarrow_{\ P(0)\rightarrow P(1)}$
3. Applying Modus Ponens to 1 and 2, we get $P(1)$. $P(1)$
4. Since $P(k)\rightarrow P(k+1)$ for all $k$, we have $P(1)\rightarrow P(2)$. $\ \Downarrow_{\ P(1)\rightarrow P(2)}$
5. Applying Modus Ponens to 3 and 4, we get $P(2)$. $P(2)$
$\vdots$   $\ \Downarrow_{\ P(k)\rightarrow P(k+1)}$
11. Applying Modus Ponens to 9 and 10, we get $P(5)$. $P(5)$

Using induction

Using induction in formal and English proofs.

Using the induction rule in a formal proof

Induction$\rule{P(0); \forall k. P(k)\rightarrow P(k+1)}{\forall n. P(n)}$

1. Prove $P(0)$  
2. Let $k\geq0$ be an arbitrary integer  
3.1. Assume that $P(k)$ is true  
3.2. $\ldots$  
3.3. Prove $P(k+1)$ is true  
4. $P(k) \rightarrow P(k+1)$ Direct Proof Rule
5. $\forall k. P(k) \rightarrow P(k+1)$ Intro $\forall$: 2, 4
6. $\forall n. P(n)$ Induction: 1, 5

Using the induction rule in a formal proof: key parts

Induction$\rule{P(0); \forall k. P(k)\rightarrow P(k+1)}{\forall n. P(n)}$

1. Prove $P(0)$  

Base case

2. Let $k\geq0$ be an arbitrary integer  
3.1. Assume that $P(k)$ is true  

Inductive
hypothesis

3.2. $\ldots$  
3.3. Prove $P(k+1)$ is true  

Inductive
step

4. $P(k) \rightarrow P(k+1)$ Direct Proof Rule
5. $\forall k. P(k) \rightarrow P(k+1)$ Intro $\forall$: 2, 4
6. $\forall n. P(n)$ Induction: 1, 5

Conclusion

Translating to an English proof: the template

① Let $P(n)$ be [ definition of $P(n)$ ].
We will show that $P(n)$ is true for every integer $n\geq 0$ by induction.
Base case ($n=0$):
[ Proof of $P(0)$. ]
Inductive hypothesis:
Suppose that $P(k)$ is true for an arbitrary integer $k\geq 0$.
Inductive step:
We want to prove that $P(k+1)$ is true.
[ Proof of $P(k+1)$. This proof must invoke the inductive hypothesis somewhere. ]
The result follows for all $n\geq 0$ by induction.
 
1. Prove $P(0)$  

Base case

2. Let $k\geq0$ be an arbitrary integer  
3.1. Assume that $P(k)$ is true  

Inductive
hypothesis

3.2. $\ldots$  
3.3. Prove $P(k+1)$ is true  

Inductive
step

4. $P(k) \rightarrow P(k+1)$ Direct Proof Rule
5. $\forall k. P(k) \rightarrow P(k+1)$ Intro $\forall$: 2, 4
6. $\forall n. P(n)$ Induction: 1, 5

Conclusion

Induction dos and don’ts:

  • Do write out all 5 steps.
  • Do point out where you are using the inductive hypothesis in step ④.
  • Don’t assume $P(k+1)$!

Example proofs by induction

Example proofs about sums and divisibility.

What is $\sum_{i=0}^{n}2^i$ for an arbitrary $n\in\N$?

Recall that $\sum_{i=0}^{n}2^i = 2^0 + 2^1 + \ldots + 2^n$.

Let’s look at a few examples:
$\sum_{i=0}^{0}2^i = 1$
$\sum_{i=0}^{1}2^i = 1 + 2 = 3$
$\sum_{i=0}^{2}2^i = 1 + 2 + 4 = 7$
$\sum_{i=0}^{3}2^i = 1 + 2 + 4 + 8 = 15$
$\sum_{i=0}^{4}2^i = 1 + 2 + 4 + 8 + 16 = 31$
It looks like this sum is $2^{n+1}-1$.
Let’s use induction to prove it!

Prove $\sum_{i=0}^{n}2^i = 2^{n+1}-1$ for all $n\in\N$

① Let $P(n)$ be $\sum_{i=0}^{n}2^i = 2^0 + 2^1 + \ldots + 2^n = 2^{n+1}-1$.
We will show that $P(n)$ is true for every integer $n\geq 0$ by induction.
② Base case ($n = 0$):
$\sum_{i=0}^{0}2^i = 2^0 = 1 = 2^{0+1} - 1$ so $P(0)$ is true.
③ Inductive hypothesis:
Suppose that $P(k)$ is true for an arbitrary integer $k\geq 0$.
④ Inductive step: Assume $P(k)$ to prove $P(k+1)$, not vice versa!
We want to prove that $P(k+1)$ is true, i.e., $\sum_{i=0}^{k+1}2^i = 2^{k+2}-1$. Note that $\sum_{i=0}^{k+1}2^i = ($$\sum_{i=0}^{k}2^i$$) + 2^{k+1} = ($$2^{k+1}-1$$) + 2^{k+1}$ by the inductive hypothesis. From this, we have that $(2^{k+1} - 1) + 2^{k+1} =$ $2 * 2^{k+1} - 1 =$ $2^{k+1+1} - 1 =$ $2^{k+2} - 1$, which is exactly $P(k+1)$.
⑤ The result follows for all $n\geq 0$ by induction.
 

Prove $\sum_{i=0}^{n}i = n(n+1)/2$ for all $n\in\N$

① Let $P(n)$ be $\sum_{i=0}^{n}i = 0 + 1 + \ldots + n = n(n+1)/2$.
We will show that $P(n)$ is true for every integer $n\geq 0$ by induction.
② Base case ($n = 0$):
$\sum_{i=0}^{n}i = 0 = 0(0+1)/2$ so $P(0)$ is true.
③ Inductive hypothesis:
Suppose that $P(k)$ is true for an arbitrary integer $k\geq 0$.
④ Inductive step:
We want to prove that $P(k+1)$ is true, i.e., $\sum_{i=0}^{k+1}i = (k+1)(k+2)/2$. Note that $\sum_{i=0}^{k+1}i = ($$\sum_{i=0}^{k}i$$) + (k + 1) = ($$k(k+1)/2$$) + (k+1)$ by the inductive hypothesis. From this, we have that $(k(k+1)/2) + (k+1) =$ $(k+1)(k/2 + 1) =$ $(k+1)(k+2)/2$, which is exactly $P(k+1)$.
⑤ The result follows for all $n\geq 0$ by induction.
 

What number divides $2^{2n}-1$ for every $n\in\N$?

Let’s look at a few examples:
$2^{2*0} - 1 = 1 - 1 = 0 = 3 * 0$
$2^{2*1} - 1 = 4 - 1 = 3 = 3 * 1$
$2^{2*2} - 1 = 16 - 1 = 15 = 3 * 5$
$2^{2*3} - 1 = 64 - 1 = 63 = 3 * 21$
$2^{2*4} - 1 = 256 - 1 = 255 = 3 * 85$
It looks like $3 \vert (2^{2n}-1)$.
Let’s use induction to prove it!

Prove $3 \vert (2^{2n}-1)$ for all $n\in\N$

① Let $P(n)$ be $3 \vert (2^{2n}-1)$.
We will show that $P(n)$ is true for every integer $n\geq 0$ by induction.
② Base case ($n = 0$):
$2^{2 * 0} - 1 = 1 - 1 = 0 = 3*0$ so $P(0)$ is true.
③ Inductive hypothesis:
Suppose that $P(k)$ is true for an arbitrary integer $k\geq 0$.
④ Inductive step:
We want to prove that $P(k+1)$ is true, i.e., $3 \vert (2^{2(k+1)}-1)$. By inductive hypothesis, $3 \vert (2^{2k}-1)$ so $2^{2k}-1 = 3j$ for some integer $j$. We therefore have that $2^{2(k+1)} - 1 $ $=$ $2^{2k+2} - 1$ $=$ $4($$2^{2k}$$) - 1$ $=$ $4($$3j+1$$) - 1$ $=$ $12j + 3 = 3(4j + 1)$. So $3 \vert (2^{2(k+1)}-1)$, which is exactly $P(k+1)$.
⑤ The result follows for all $n\geq 0$ by induction.
 

Summary

Fast modular exponentiation efficiently computes $\mod{a^k}{m}$.
Important practical applications include public-key cryptography (RSA).
Induction lets us prove statements about all natural numbers.
A proof by induction must show that $P(0)$ is true (base case).
And it must use the inductive hypothesis $P(k)$ to show that $P(k+1)$ is true (inductive step).